Directing solar photons to sustainably meet food, energy, and water needs - Emre Gençer (Nature Portfolio, 2017)
Abstract As we approach a “Full Earth” of over ten billion people within the next century, unprecedented demands will be placed on food, energy and water (FEW) supplies. The grand challenge before us is to sustainably meet humanity’s FEW needs using scarcer resources. To overcome this challenge, we propose the utilization of the entire solar spectrum by redirecting solar photons to maximize FEW production from a given land area. We present novel solar spectrum unbundling FEW systems (SUFEWS), which can meet FEW needs locally while reducing the overall environmental impact of meeting these needs. The ability to meet FEW needs locally is critical, as significant population growth is expected in less-developed areas of the world. The proposed system presents a solution to harness the same amount of solar products (crops, electricity, and purified water) that could otherwise require ~60% more land if SUFEWS were not used—a major step for Full Earth preparedness.